Update on the epidemiology of work-related traumatic brain injury: a systematic review and meta-analysis - Toccalino, Danielle; Colantonio, Angela; Chan, Vincy (Occupational and environmental medicine (London, England), 2021)
BackgroundTraumatic brain injury (TBI) is a public health concern that can occur in a range of contexts. Work-related TBI (wrTBI) is particularly concerning. Despite overall work-related injury claims decreasing, the proportion of claims that are wrTBI have increased, suggesting prevention and support of wrTBI requires ongoing attention.ObjectivesThis review aimed to provide updated information on the burden and risk factors of wrTBI among the working adult population.MethodsMedline, Embase, PsycINFO, and Cumulative Index to Nursing and Allied Health Literature (CINAHL) were searched using a combination of TBI, work, and epidemiology text words and medical subject headings. Two reviewers independently assessed articles for inclusion. Meta-analyses were conducted to estimate prevalence and mortality of wrTBI and a narrative synthesis was conducted to provide additional context.ResultsPooled proportions meta-analyses estimate that 17.9% of TBIs were work-related and 6.3% of work-related injuries resulted in TBI, with 3.6% of wrTBI resulting in death. Populations of wrTBI were predominantly male (76.2%) and were 40.4 years of age, on average. The most commonly reported industries for wrTBI were education and training, healthcare and social assistance, construction, manufacturing, and transportation. Falls, being struck by an object or person, motor vehicle collisions, and assaults were the most commonly reported mechanisms of wrTBI.ConclusionsA better understanding of the epidemiology of wrTBI can inform prevention and management strategies. This review highlights existing gaps, including a notable lack of sex or gender stratified data, to direct future investigation.PROSPERO registration numberCRD42020169642.